A new (singleton) rainfrog of the Pristimantis myersi Group (Amphibia: Craugastoridae) from the northern Andes of Ecuador - Guayasamín, Juan (2018)
Reserva Las Gralarias is one of the best-studied localities of the Ecuadorian Andes in terms of its batrachofauna. However, as expected in any community, some species are rare and, therefore, their discovery and description are problematic. Herein, based on a single specimen, we describe Pristimantis gralarias sp nov. Even though we are aware of the problems associated to singleton species (i.e., unknown intraspecific variation, limited ecological information), our efforts to finding additional specimens have been unsuccessful. Thus, given the importance of species descriptions in threatened areas (e.g. Andes), and that the new taxon is supported by both morphological and genetic data, we consider that the description is justified. Pristimantis gralarias sp nov is easily distinguished from all other members of the P. myersi group by its long and slender fingers and toes, with discs that are not expanded laterally (or are only slightly expanded). Furthermore, the new species is characterized by having a black venter with minute white spots and a red groin. A molecular phylogeny corroborates the placement of the new species in the P. myersi group and its distinctiveness in relation to other species. Finally, we discuss on the limitations and advantages associated to species descriptions based on one or few specimens. Copyright © 2018 Magnolia Press.